Hotstar: Holographic of Astronomical Objects - Qudsy, Cintamani Zahrotul; Darmawan, Almira; Angelica, Inggrid Twi; Ridwan, Mohammad (University of Muhammadiyah Sumatera Utara, 2024)
In order to answer the world's challenges related to the development of science from generation to generation, this study discusses the introduction of astronomy as one of the disciplines that affects several aspects of life, such as in the calculation of the time of worship of religious people (Islam), the determination of time in each region in various parts of the world, and so on, which in this case is juxtaposed with the pace of technological progress along with the development of the world. is increasing. In the content of the discussion related to astronomical orientation, the researcher also included the history of the development of astronomy along with previous Muslim astronomers with their various discoveries. This research also frames a series of astronomical introductions through technology in the form of simple holograms used to visualize astronomical objects. By using a qualitative research method conceptualized through the trial of visual-interactive products in the form of simple holography-based props, Hotstar is designed to orient the field of astronomy science to the general public with simple hologram visualization. The final results of the trial stated that 90% of respondents were satisfied with the Hotstar teaching aids and this research will also continue to be developed to increase interactivity in material exposure and astronomical orientation in the future.